Hubungan Motivasi Belajar dan Beban Kognitif dengan Moderasi Multimedia Interaktif pada Pembelajaran Matematika - Nur Adni Azisah; Fitri; Alya Anwar; A. Muhajir Nasir (Program Studi Pendidikan Matematika, FKIP Universitas Muslim Maros, 2025)
This study aims to analyze the relationship between learning motivation and cognitive load among elementary school students in mathematics learning, and to examine whether interactive multimedia instruction moderates this relationship. A quantitative correlational design was employed. Participants were elementary school students who experienced two different instructional conditions: interactive multimedia learning and conventional learning. Data were collected using a motivation scale based on the ARCS model and a cognitive load scale developed according to Cognitive Load Theory. Data analysis was conducted using Pearson correlation and Moderated Regression Analysis (MRA). The results indicate a significant negative relationship between learning motivation and cognitive load (r = −0.361, p = .007), suggesting that higher motivation is associated with lower perceived cognitive load. However, the moderation analysis revealed that the type of instruction did not significantly moderate the relationship between learning motivation and cognitive load (p = .173), indicating that the effect of motivation remained consistent across both instructional conditions. These findings highlight the role of motivation as an important psychological factor affecting cognitive processing in mathematics learning. Meanwhile, the use of multimedia requires careful instructional design to ensure that it contributes effectively without increasing unnecessary cognitive demands.